Utveckling av differentierade transportersättningar för rundvirskestransporter med lastbil - Lindström, Elin (SLU/Dept. of Forest Resource Management, 2010)
Approximately 60 million cubic meters of round wood are transported every year with trucks in Sweden and stand for 15 % of all truck transportation in the country. The big amount that is transported results in many haulage companies works in different parts of the country with different conditions to get a good flow on their transports. Today the transport pricing is very general and the payment consists of the unit round wood they are transporting and the distance of the transport.